Agama dan Marketplace : Muslim Baru Sebagai Arus Utama Dalam Pertumbuhan Ekonomi Global - Dede Aji Mardani (La Zhulma | Jurnal Ekonomi dan Bisnis Islam, 2022)
The purpose of this study is to analyze the impact of Muslim consumers both Indonesia and globally in contributing to GDP as a whole, through the marketplace. In addition, how are the concepts and ethics used by global Muslim consumers in making purchase transactions in the marketplace. The method used is a qualitative method with a formal ontology analysis content approach from the unity of the religious and economic fields built within the realm of interconnecting and organically integrated moral, social and economic values. A phenomenological model of an integrated world view that applies to systemic concepts. The results show that there are four forms of Muslims in accepting share with marekeplace 1) rationalist 2) affective 3) apathetic 4) compromising. Meanwhile, the contribution of Muslim income to the global market sector shows that there are four main currents of Muslims in transactions, namely the creation of a new Muslim market share, 2) the middle class of Muslims, 3) the role of immigrants in forming new markets and the creation of a new Muslim road map (Muslim resegregation).